Determinants of Customer Satisfaction of BMT Mitra Ummat With SERVQUAL Approach - Trisma Kamelia; Fuad Hasyim; Dea Primi Purnamasari (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2023)
Baitul Maal wa Tamwil is one of the Islamic financial institutions, where increasing customer satisfaction is a priority that must be done. This is done because of the intense business competition in financial institutions. There is satisfaction from customers, the existence of Baitul Maal wa Tamwil can be maintained. The way that can be done to increase customer satisfaction is by providing the best service. The purpose of this study is to determine and analyze the effect of service quality consisting of reliability, emphaty, responsiveness, tangible, and assurance variables on customer satisfaction of BMT Mitra Ummat. Sampling using accidental sampling with the distribution of questionnaires to BMT Mitra Ummat customers. Primary data were analyzed using multiple regression. The results show that the Tangible Variable affects the customer satisfaction of BMT Mitra Ummat. Where obtained a t value of 6.509 with a significant value of 0.000 < 0.05 means that Ha is accepted and Ho is rejected. The Reliability variable does not affect the customer satisfaction of BMT Mitra Ummat. Where obtained a value of t of -1.443 with a significant value of 0.152 > 0.05 means that Ha is rejected and Ho is accepted. The Responssive variable has no effect on customer satisfaction of BMT Mitra Ummat. Where obtained a t value of -3.019 with a significant value of 0.003 < 0.05 means that Ha is rejected and Ho is accepted. The Assurance variable has no effect on customer satisfaction of BMT Mitra Ummat. Where obtained a t value of 1.798 with a significant value of 0.075 > 0.05 means that Ha is rejected and Ho is accepted. The Empathy variable affects the customer satisfaction of BMT Mitra Ummat. Where obtained a t value of 5.604 with a significant value of 0.000 < 0.05 means that Ha is accepted and Ho is rejected. In the research conducted by (Dibyantoro, 2012) where the results obtained were all variables of service quality affecting Customer Satisfaction at PT Bank BTN Palembang branch. However, it is different from this study where the results of the Tangible and Empathy variables affect the Customer Satisfaction of BMT Mitra Ummat, while the variables of Reliability, Responsiveness and Assurance do not affect the satisfaction of BMT Mitra Ummat customers.